Securities Clearance and Settlement Systems : A Guide to Best Practices - Guadamillas, Mario (World Bank, Washington, DC, 2014)
As an essential part of a nation's financial sector infrastructure, securities clearance, and settlement systems must be closely integrated with national payment systems, so that safety, soundness, certainty, and efficiency can be achieved at a cost acceptable to all participants. Central banks have paid considerable attention to payment systems, but securities clearance, and settlement systems have only recently been subjected to rigorous assessment. The Western Hemisphere Payments and Securities Clearance and Settlement Initiative (WHI), led by the World Bank, and in cooperation with the Centro de Estudios Monetarios Latinoamericanos (CEMLA), gave the authors a unique opportunity to observe how various countries in Latin America, and the Caribbean undertake securities clearance, and settlement. To do so, the authors developed a practical, and implementable assessment methodology, covering key issues that affect the quality of such systems. In this paper they discuss the objectives, scope, and content of a typical securities system, identify the elements that influence the system's quality, and show how their assessment methodology works. They focus on the development of core principles, and minimum standards for integrated systems of payments, and securities clearance and settlement. Their paper fills a gap by providing an evaluation tool for assessors of such systems, especially those who must assess evolving systems in developing, and transition economies. Essentially, an assessment involves a structured analysis to answer four related questions: 1) What are the objective, and scope of a securities clearance and settlement system? 2) Who are the participants, what roles do they play, and what expectations do they have? 3) What procedures are required to satisfy the participants' needs? 4) What inherent risks are involved, and how can they be mitigated at an acceptable cost?